Hidden gems and borrowers with dirty little secrets: investment in soft information, borrower self-selection and competition - Reint E. Gropp; Christian Gruendl; Andre Guettler (European Central Bank (ECB), 2013)
This paper empirically examines the role of soft information in the competitive interaction between relationship and transaction banks. Soft information can be interpreted as a private signal about the quality of a firm that is observable to a relationship bank, but not to a transaction bank. We show that borrowers self-select to relationship banks depending on whether their privately observed soft information is positive or negative. Competition affects the investment in learning the private signal from firms by relationship banks and transaction banks asymmetrically. Relationship banks invest more; transaction banks invest less in soft information, exacerbating the selection effect. Finally, we show that firms where soft information was important in the lending decision were no more likely to default compared to firms where only financial information was used.
Keywords: G21; G28; G32; 330; competition; discretionary lending; relationship lending; soft information